2022
DOI: 10.29228/jrp.198
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of drug-related problems in pediatric inpatients by clinical pharmacist-led medication review: An observational study

Abstract: It is well-known that problems related to pharmacotherapy affect pediatric patients' therapy outcomes. Evaluating pharmacotherapy by a clinical pharmacist in pediatric clinics could ameliorate drug-related problems (DRPs). This study aimed to identify and compare the prevalence and types of DRPs in pediatric patients in two study phases: the prospective phase while providing clinical pharmacist-led medication review service and the retrospective phase among subjects obtained by age-sex-diagnose-matching accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…Although not directly focused on the pediatric population, a study assessing the efficacy of HMR in geriatric hypertensive patients demonstrated the effectiveness of this approach in resolving drug-related problems (DRPs), suggesting that similar benefits could be observed in younger populations [8]. Clinical pharmacist-led medication reviews in pediatric inpatients have shown potential in detecting DRPs, highlighting the importance of involving pharmacists in direct patient care to improve medication safety [9]. Furthermore, an impact analysis of pharmacist-led HMR within an interprofessional outreach team for frail and homebound older adults identified a high number of medications and significant DRPs, indicating that HMRs could be an effective method to optimize medication therapy in the pediatric population as well [10].…”
Section: Discussionmentioning
confidence: 99%
“…Although not directly focused on the pediatric population, a study assessing the efficacy of HMR in geriatric hypertensive patients demonstrated the effectiveness of this approach in resolving drug-related problems (DRPs), suggesting that similar benefits could be observed in younger populations [8]. Clinical pharmacist-led medication reviews in pediatric inpatients have shown potential in detecting DRPs, highlighting the importance of involving pharmacists in direct patient care to improve medication safety [9]. Furthermore, an impact analysis of pharmacist-led HMR within an interprofessional outreach team for frail and homebound older adults identified a high number of medications and significant DRPs, indicating that HMRs could be an effective method to optimize medication therapy in the pediatric population as well [10].…”
Section: Discussionmentioning
confidence: 99%